Traumatic Exogenous Uveitis - Williams, Melanie M.; Wilcock, B. P. (Veterinary and Comparative Orthopaedics and Traumatology, 1988)
A young dog was presented to the veterinary ophthalmology service with marked unilateral anterior uveitis and blindness, extreme pain, anorexia and weight loss. Porcupine quill migration into the orbital and ocular tissues was suspected due to an encounter with a porcupine three weeks previously. Surgical orbital extenteration and exploration revealed two porcupine quill segments penetrating the oculus bulbi and extending into the orbital tissues. The location and movement of the quills within the globe and orbital muscle cone during mastication accounted for the deep pain, anorexia and weight loss. The quills incited a sterile foreign body reaction with fibroplasia and granulation tissue formation in the sclera and ciliary body. The eye was avisual due to the anterior segment structural and inflammatory changes.
Keywords: Porcupine quill migration; Anterior uveitis; Orbital extenteration; Foreign body reaction